High AdiponectinHormone Modulation ofBlood Erythroid Parameters and its Relation with Erythropoietin in Patients with Diabetic Nephropathy - Hayder, Zhian Sherzad; Kareem, Zrar Saleem (Iraqi Journal of Science, 2020)
Background: Serum adiponectin is a hormone of adipose tissue that activateslipid metabolism and exertsphysiological functions. Its level usually fluctuates in several metabolic diseases,including renal insufficiency and diabetes; it loses its protective role against diseases and becomes a potentially risk factor for erythroid abnormalities.Objectives: The study was designed to assess the association between adiponectin hormone, blood erythroid and various parameters in groups of patients.Method:The study included 130 patientsand 42 healthy subjects. Parameters of serum adiponectin, erythropoietin (EPO), red blood cells (RBC), hemoglobin (Hb), hematocrit (Hct), renal function, serum insulin, fasting blood sugar (FBS), glycated hemoglobin % (HbA1c%) and homeostatic model assessment of insulin resistance (HOMA-IR) were estimated in all groups.Result: Statistical analysis showed that high level of adiponectin was significantly associated with erythroid-related variables (EPO, RBC, Hb and Hct) in patients groups when compared with the control. Receiver Operating Characteristic (ROC) curve analysis showed that adiponectin is a significant risk factor for anemia progression in non-insulin dependent diabetes mellitus (NIDDM), end stage renal disease (ESRD)and diabetic nephropathy patients.Conclusion: We suggest that high serum adiponectin level is dependently associated with EPO level and erythroid abnormalities in NIDDM, kidney failure and diabetic nephropathy patients. The present findings regarding ROC curve analysis of adiponectin suggested that this hormone could represent a risk factor for erythroid abnormality in diabetic nephropathy at ESRD.